The epidemiological characteristics, clinical manifestations, and outcomes of individuals diagnosed with COVID-19 infection at Al-Salama, Al-Ameria Hospital, during the period of April to August 2022. - Atshan, Fawzi Hashim; Hasan, Ibtisam Faraj; Ghali, Ehab Jumaa; Alsherees, Hashim (Medical Science Journal for Advance Research, 2023)
Background: The majority of individuals who contract COVID-19, a disease caused by a novel coronavirus, are capable of recuperating at home without requiring hospitalization. However, elderly individuals and those with pre-existing medical conditions, such as heart disease, diabetes, chronic lung disease, or cancer, are at a greater risk of developing severe illnesses and may require hospitalization. The objective of this study: is to provide a detailed account of the epidemiology, clinical manifestations, and outcomes of COVID-19 patients who were admitted to Al-Salama Hospital, Al-Ameria, Baghdad, Iraq. Method: In this study, a retrospective analysis was conducted to investigate cases of COVID-19 infection that were admitted to Al-Salama Hospital, located in Al-Ameria, of Al-Karkh Health Directorate in Baghdad. Demographic data, clinical presentation, and outcomes were extracted using a specialized form. Results: The study included 101 cases admitted to Al-Salama Hospital from April to August 2022, out of which 87 were confirmed positive for COVID-19 through PCR testing while 14 were not tested. Among those who were tested, 5 cases tested negative and were discharged, while 9 cases tested positive, resulting in a total of 96 diagnosed cases of COVID-19.The duration of hospitalization was determined based on the severity of the illness. Moderate-severe cases (85/96) were discharged improved after a hospital stay of 3-7 days, while severe-critical cases (11/96) resulted in fatalities. The primary causes of death were respiratory failure and sepsis, and the patients stayed in the hospital for 8-21 days. Of the cases studied, 35/96 had been vaccinated against COVID-19. Out of the 11 deceased patients, 9 had a history of vaccination, while 26/85 of the discharged patients had been immunized. Males accounted for 56% of the cases, and the age range of 60-69 years had the highest number of male patients. Most female patients were in the age group of 80-95 years. The distribution of hospital admissions followed a trend similar to the 3rd and 5th waves of the epidemic that hit Iraq in July 2021 and 2022, respectively. Respiratory symptoms were the most common clinical presentation (74%), followed by gastrointestinal symptoms (12%), headache (8%), and chest pain (7%). Comorbidities were prevalent, with hypertension (43%), diabetes mellitus (32%), and cardiovascular disease (15%) being the most common. Conclusions: In conclusion, the findings of this study may have implications not only for Al-Salama Hospital Al-Ameria in Iraq but also for other countries with comparable epidemiological and clinical characteristics and disease outcomes during the pandemic.